Relationship between shooting performance and motoric characteristics, respiratory function test parameters of the competing shooters in the youth category - Yapici, A.; Bacak, C.; Çelik, E. (European Journal of Physical Education and Sport Science, 2018)
Shooting is a high precision sport, where high level performance requires several physical capacities, striking control, experience, posture control and skill of a shooter. The purpose of this study is to investigate the relationship between the shooting performance and physical capacities of the competing shooters. A total of 19 shooters participated as volunteers in the Turkish Championship youth category. Anthropometric measurements and shooting scores were recorded. Hand grip strength, flexibility, reaction time, dynamic balance, maximal oxygen consumption and respiratory function tests were applied. The correlation between shooting performance and respiratory function parameters, motoric characteristics were examined by Pearson Correlation analysis. A statistically significant correlation was found between the flexibility and shooting performance (p<0.05). There was a statistically significant correlation between right-left hand grip strengths and shooting performance (p<0.05). There was no statistically significant correlation between shooting performance and reaction time, respiratory function parameters, endurance, balance parameters (p>0.05). Motoric properties and respiratory control are important factors for successful shooting. The results of this study can provide for trainers for determining the developments and deficiencies of the different age group shooters at the point of preparation of the training plan by determining the motor characteristics during the season.